Plastic Use Sustainable Change in Portugal: An Analysis on Tourism Stakeholders’ Actions and Programmes - Nunes, Dília; Lessa, Joana (Journal of Tourism, Sustainability and Well-being, 2021)
Studies indicate that 80 % of all Tourism in Europe is held in coastal areas. In Portugal the number grows to 90 %, a fact that raises two distinct but equally relevant types of concerns: on one side the pressure for maintaining the shorelines and beaches clean and aesthetically appraisable for visitors, and on the other side, the potential massification of tourism that stands on the opposite end towards preserving the environment of tourism locations. This study focuses on the relevance of the oceans’ preservation for the tourism sector in Portugal, specifically in the Algarve, and on how sustainability is being addressed regarding plastic use and its negative outcome, particularly marine litter and the damages it inflicts on coastal areas. The methodology adopted was literature review and case studies analysis of a set of governmental, non-governmental and private tourism sector stakeholder’s actions and programmes. Findings suggest that the promotion of circular economy is a path several organizations are already undertaking in order to address plastic use towards a more sustainable planet and Tourism development. Results also indicate that Design is an important facilitator for the change of the tourism sector towards this new circular economy model.